Pengaruh Penerapan Pendekatan Saintifik dan Power Point terhadap Keaktifan Belajar Siswa pada Pembelajaran Pendidikan Agama Islam - Razali Pebrianto (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2019)
This study aims to see whether there is an influence of the application of scientific approach and power point based learning on student learning activities in State Junior High Schools in Sukajadi District, Pekanbaru City. The sample in this study was taken by proportionate random sampling technique with 10% of the total pollution that is 226 people. Technique of analysis using multiple regression analysis. The results of this study indicate the value of R2 (coefficient of determination) or r square of 0.796 or 79.6%. This value can be interpreted that the change in student learning activeness by changing the value of the independent variable applying the scientific approach and power point based learning is 79.6% while 20.4% is determined by changes in other factors that are not present in the model. T value for the variable of applying the scientific approach is 3.023 with sig. 0.003 less than 0.05 this means that there is an effect of the application of the scientific approach to student learning activeness and t for the teacher performance variable is 25,581 with sig. 0,000 is less than 0.05 which means there is an effect of power point-based learning on student learning activeness.